The Prognostic Value of External vs Internal Pancreatic Duct Stents in CR-POPF after Pancreaticoduodenectomy: A Systematic Review and Meta-analysis - Yuancong Jiang; Qin Chen; Zhize Wang; Yi Shao; Chen Hu; Yuan Ding; Zhenhua Shen; Ming Jin; Sheng Yan (Journal of Investigative Surgery, 2021)
Background There is no specific evidence regarding the benefits of external and internal pancreatic duct stents after pancreaticoduodenectomy since pancreatic fistula (grade A) have been redefined with no clinical treatment effect. We aimed to reevaluate the prognostic value of external and internal stents in clinically relevant postoperative pancreatic fistula over pancreaticoduodenectomy. Methods PubMed, Web of Science, EMBASE and the Cochrane Database were specifically searched for pertinent and original articles published before May 2019. The project has been registered in PROSPERO (Registration number: CRD42019137579). Results Four randomized controlled trials and six nonrandomized controlled trials with a total of 2101 patients were enrolled in this meta-analysis. The use of an external stent resulted in better performance than the use of an internal stent in terms of pancreatic fistula (grade C) (OR 0.58, P = 0.03) but did not reduce the rate of pancreatic fistula (grade B) (OR 0.99, P = 0.94) in all studies. The meta-analysis of randomized controlled trials found that the use of an external stent approached a level of significance for an increased rate of clinically relevant postoperative pancreatic fistula compared to the use of an internal stent (OR 1.40, P = 0.10) but had no significant effect on pancreatic fistula (grade B) (OR 1.34, P = 0.26) or pancreatic fistula (grade C) (OR 1.68, P = 0.62). Conclusion Compared with internal stents, the use of external stent might be associated with a lower rate of pancreatic fistula (grade C). More randomized clinical trials are warranted to further explore safety and efficacy of pancreatic duct external stents.